Assessment of rimonabant-like adverse effects of purported CB1R neutral antagonist / CB2R agonist aminoalkylindole derivatives in mice. (1st November 2018) - Tai, Sherrica; Vasiljevik, Tamara; Sherwood, Alexander M.; Eddington, Sarah; Wilson, Catheryn D.; Prisinzano, Thomas E.; Fantegrossi, William E.
Highlights: TV-5-249 and TV-6-41 function as neutral CB1R antagonists and full CB2R agonists. Neither showed CB1R agonist effects; neither induced rimonabant-like scratching. Rimonabant and TV-5-249 induced taste aversion, but TV-6-41 did not. Rimonabant elicited dramatic withdrawal signs, but TV-6-41 did not. Combining neutral CB1R antagonism with CB2R agonism may be useful in drug dependence. Abstract: Background: Cannabinoids may be useful in the treatment of CNS disorders including drug abuse and addiction, where both CB1R antagonists / inverse agonists and CB2R agonists have shown preclinical efficacy. TV-5-249 and TV-6-41, two novel aminoalkylindoles with dual action as neutral CB1R antagonists and CB2R agonists, previously attenuated abuse-related effects of ethanol in mice. Purpose: To further characterize these drugs, TV-5-249 and TV-6-41 were compared with the CB1R antagonist / inverse agonist rimonabant in assays relevant to adverse effects and cannabinoid withdrawal. Procedures and findings: The cannabinoid tetrad confirmed that TV-5-249 and TV-6-41 were devoid of CB1R agonist effects at behaviorally-relevant doses, and neither of the novel drugs induced rimonabant-like scratching. Generalized aversive effects were assessed, and rimonabant and TV-5-249 induced taste aversion, but TV-6-41 did not. Schedule-controlled responding and observation of somatic signs were used to assess withdrawal-like effects precipitated by rimonabant or TV-6-41 in mice previously treated with the high-efficacy CB1R agonist JWH-018 or vehicle. Rimonabant and TV-6-41 dose-dependently suppressed response rates in all subjects, but TV-6-41 did so more potently in JWH-018-treated mice than in vehicle-treated mice, while rimonabant equally suppressed responding in both groups. Importantly, rimonabant elicited dramatic withdrawal signs, but TV-6-41 did not. Conclusions: These findings suggest differences in both direct adverse effects and withdrawal-related effects elicited by rimonabant, TV-5-249, and TV-6-41, which could relate to neutral CB1R antagonism, CB2R agonism, or a combination of both. Both mechanisms should be explored and exploited in future drug design efforts to develop pharmacotherapies for drug dependence.